Vibration Performance Redistribution in Heterogeneous Networks. (22nd December 2020) - Huang, Genling; Wang, Jiqiang
Abstract : Collective behaviors such as synchronization, consensus, and flocking have been extensively investigated over the past decades. Many important results have been disseminated concerning the properties of complex networks. Recent technological development requires performance distribution, and this motivates the resolution to the issue of performance distributability. Albeit in a simple setup, this paper presents an attempt to attacking this problem. Important results are obtained for performance redistribution under both unitary and specified specifications. Constraints are also considered revealing the tight bounds on both nodes dynamics and graph elements for fulfilling the performance distribution and redistribution requirements. Examples are presented for verification of the claims.